Rationalization of a traditional liver medicine using systems biology approach and its evaluation in preclinical trial. (February 2020) - Adhikari, Aniruddha; Darbar, Soumendra; Das, Monojit; Mondal, Susmita; Sankar Bhattacharya, Siddhartha; Pal, Debasish; Kumar Pal, Samir
Graphical abstract: Highlights: A combined computational and experimental approach for rationalization and repurposing of traditional medicine. The method accurately predicts active ingredients of a polyherbal extract (or extract from other biological sources). It also computes the molecular mechanism of action of the active ingredients. The results are verified with animal studies. This unique method can reduce the time and cost of the conventional drug discovery process. Abstract: 'Bottom-up', i.e., molecule to medicine strategy for the discovery of new drugs takes enormous time and cost. In most of the cases, inherent toxicity and undesired side effects of the developed drug hinder its way beyond the early stages of development. In this regard, the systems pharmacology can play an excellent role by reducing the cost and time of drug development through rationalization and/or repurposing of traditional drugs with known side effects. In the present study, our aim was to develop an integrated systems biology method for the prediction of active ingredients of a traditional medicine and their potential targets inside the body. Further, we evaluated the predictive capacity of the developed method in a preclinical animal model. Here, we have prepared a formulation (SKP17LIV01) from an extract of eight medicinal plants traditionally used as liver medicine and identified the constituents using UHPLC-MS technique. Using systems biology approach, we have rationalized the components of the formulation for potential use in the treatment of heavy metal-induced hepatotoxicity. The active ingredients and potential therapeutic targets were also predicted. A detailed biochemical, histopathological and molecular study on the mice model of lead toxicity confirms the efficacy of the formulation as per prediction by the systems pharmacology approach. The study may open a new frontier for re-discovery of drugs that are already used in traditional medicine.